TINJAUAN KEPEMILIKAN DALAM KPR SYARIAH: ANTARA MURABAHAH, IJARAH MUNTAHIYYAH BITTAMLIK, DAN MUSYARAKAH MUTANAQISAH (Equilibrium: Jurnal Ekonomi Syariah, 2013)
The house is a basic need, but not everyone has the purchasing power. This opportunity is exploited by the Islamic banking with Sharia mortgages or Financing Home Ownership. There are three financing agreement used by mortgage banks in the Shari’ah ie murabaha contract, Muntahiyyah bittamlik ijara contract, and Musharaka mutanaqisah contract. This study uses the method based on litelature aimed to uncover how the implementation of the contractagreement in the main Islamic banks in the matter of ownership. Of studies conducted found a mismatch between the Islamic principles of positive law which has been applied in the third contract. The problems relating wakalah contract, and their impact on ownership.